Impact of a dedicated center for atrial fibrillation on resource utilization and costs. Issue 3 (20th January 2023) - Medhekar, Ankit; Mulukutla, Suresh; Adams, Whitney; Kristofik, Amanda; Byers, Erica; Thoma, Floyd; Aronis, Konstantinos; Barrington, William; Bazaz, Raveen; Bhonsale, Aditya; Estes, Nathan Anthony Mark; Kancharla, Krishna; et al.
Abstract: Background: Atrial fibrillation (AF) affects millions of Americans each year and can lead to high levels of resource utilization through emergency department (ED) visits and inpatient stays. Hypothesis: We hypothesized that referral of patients to a dedicated Center for AF from the ED would reduce costs of care. Methods: The University of Pittsburgh Center for AF serves as a rapid referral center for patients with AF to avoid unnecessary inpatient admissions and provide specialized care. Patients that presented to the ED with AF and met prespecified criteria were directed to rapid outpatient follow‐up instead of inpatient admission. The primary outcome of interest was 30‐day total costs. Secondary outcomes included outpatient costs, inpatient costs, 90‐day costs, and inpatient stay characteristics. Results: We identified 96 patients (median age 65, 38% women) referred to the center for AF for a new diagnosis of AF between October 2017 and December 2019 and matched 96 control patients. After 30 days of follow‐up, patients referred to the center for AF had a lower average cost ($619 vs. $1252, p  < 0.001) compared to controls, driven by lower costs of ED care tempered by slightly higher outpatient costs. Thirty‐day admissions and lengths of stay were also lower. These differences were persistent at 90 days. Conclusion: Directing patients with AF that present to the ED to follow‐up at a dedicated Center for AF significantly reduced overall costs, while reducing subsequent inpatient admissions and total lengths of stay in the hospital.